Single-cell transcriptomes reveal a molecular link between diabetic kidney and retinal lesions - Ying Xu; Zhidan Xiang; Weigao E; Yue Lang; Sijia Huang; Weisong Qin; Jingping Yang; Zhaohong Chen; Zhihong Liu (Communications Biology, 2023)
Abstract The occurrence of diabetic nephropathy (DN) and diabetic retinopathy (DR) are closely associated in patients with diabetes. However, the cellular and molecular linkage of DN and DR has not been elucidated, and further revelations are needed to improve mutual prognostic decisions and management. Here, we generate and integrate single-cell RNA sequencing profiles of kidney and retina to explore the cellular and molecular association of kidney and retina in both physiological and pathological conditions. We find renal mesangial cells and retinal pericytes share molecular features and undergo similar molecular transitions under diabetes. Furthermore, we uncover that chemokine regulation shared by the two cell types is critical for the co-occurrence of DN and DR, and the chemokine score can be used for the prognosis of DN complicated with DR. These findings shed light on the mechanism of the co-occurrence of DN and DR and could improve the prevention and treatments of diabetic microvascular complications.